2021
DOI: 10.1051/0004-6361/202141254
|View full text |Cite
|
Sign up to set email alerts
|

Radio study of HESS J1857+026: Gamma-rays from a superbubble?

Abstract: Aims. We provide new insights into the nature of HESS J1857+026, a very-high-energy γ-ray source whose complex morphology in the TeV band was attributed to the superposition of two distinct sources. Methods. We performed radio continuum observations to look for the pulsar wind nebula and the supernova remnant associated with the pulsar PSR J1856+0245, which might be powering part of the γ-ray emission. We observed HESS J1857+026 with the Karl G. Jansky Very Large Array (VLA) at 1.5 GHz in the C configuration. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 36 publications
(36 reference statements)
1
9
0
Order By: Relevance
“…The characteristic age and spin-down luminosity of PSR J1857+0300 are τ c ∼ 4.6 × 10 6 yr and  ~´-E 2.3 10 erg s 32 1 , with a distance of ∼6.7 kpc. Meanwhile, an elliptical superbubble was detected with a neutral gas observation (Petriella et al 2021), which is also spatially coincident with HESS J1857+026. The kinematical distance of the superbubble is about 5.5 kpc and is close to the DM distance of PSR J1856+0245 (∼6.3 kpc).…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…The characteristic age and spin-down luminosity of PSR J1857+0300 are τ c ∼ 4.6 × 10 6 yr and  ~´-E 2.3 10 erg s 32 1 , with a distance of ∼6.7 kpc. Meanwhile, an elliptical superbubble was detected with a neutral gas observation (Petriella et al 2021), which is also spatially coincident with HESS J1857+026. The kinematical distance of the superbubble is about 5.5 kpc and is close to the DM distance of PSR J1856+0245 (∼6.3 kpc).…”
Section: Introductionmentioning
confidence: 53%
“…For the possible origin of the gammaray emission from HESS J1857+026, MAGIC Collaboration et al (2014) suggested a PWN powered by PSR J1856+0245 with  = É 4.6 10 36 erg s −1 , and the spin-down luminosity of PSR J1857+0300 with  ~´-E 2.5 10 erg s 32 1 is too low to power a gamma-ray PWN (Abdo et al 2013;Acero et al 2013). Petriella et al (2021) revealed the existence of a superbubble with the analysis of atomic gas in this region and suggested a superbubble origin for the TeV emission from HESS J1857+026. However, the hard GeV gamma-ray spectrum of HESS J1857+026 makes it different from the typical superbubble with an index of ∼2.2, e.g., Cygnus Cocoon (Ackermann et al 2011;Aharonian et al 2019), but is similar to the typical PWNe, e.g., MSH 15-52 (Abdo et al 2010a) For PWNe, the emission from radio to X-rays is normally produced by the synchrotron emission, whereas the gamma-ray emission is explained by the IC scattering process (the leptonic process).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations